Isolation of entomopathogenic fungus, Aspergillus flavus and its efficacy against cotton mealy bug (Phenacoccus solenopsis) - G, RAMYA VAIDEKI; T S, RAMYAA LAKSHMI (The Indian Journal of Agricultural Sciences, 2025)
Phenacoccus solenopsis is commonly known as cotton mealy bug is a harmful pest that affects cotton (Gossypium spp.) plants as well as ornamental plants and other agricultural products due to its ability to feed on a wide variety of plants. The experiment was conducted during 2023 at Thiagarajar College, Madurai, Tamil Nadu to investigate the potential of the entomopathogenic fungus Aspergillus flavus as a control method for the 3rd nymphal instar of solenopsis in the laboratory assay. The entomopathogenic fungi were isolated from soil by Galleria bait method. The pathogenicity of the fungi was evaluated through dipping bioassays using three different concentrations of conidial suspensions (1×106, 1×107 and 1×108) and a negative control of 0.05% Tween 80. The experiments were repeated three times, each with 25 insects. The results showed that A. flavus was effective in killing the pest, with a mortality rate of 89.3% after 120 h. The pathogenicity of A. flavus was further analyzed through histological studies. The GC-MS analysis of the ethyl acetate extract of A. flavus confirmed the presence of insecticidal compounds such as pthalic acid and dibutyl phthalate. Results indicated that A. flavus shows promise as a biocontrol agent against solenopsis and could be considered for use in field applications.